Developments and conflicts regarding the classification of mental disorders in DSM-5: A review of the scientific dialogue and critique - Μούτσου, Ειρήνη; Γεωργάκα, Ευγενία (Psychology: the Journal of the Hellenic Psychological Society, 2020)
The fifth edition of the Diagnostic and Statistical Manual of Mental Disorders (DSM- 5) was released by the American Psychiatric Association in May 2013 and has provoked a broad scientific discussion, since it entails significant changes in relation to its previous editions. The current paper offers a review of this discussion, with emphasis on the main changes that are under dispute. Initially, we discuss the developmental course of the various editions of the DSM, the main principles and practices of the current edition as well as the main points of critique against it. We then examine in more detail some significant changes in particular diagnostic categories and their expected implications for the diagnosis and treatment of these mental disorders. In conclusion, the main critique against DSM-5 is that it seems to intensify the medicalisation of mental disorders, which characterises its latest editions, to pathologise a range of everyday experiences and behaviours, and to broaden the diagnosed population, especially to children and the elderly, expanding possibly the use of medication to new age groups.